2013
DOI: 10.1016/j.jacc.2013.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Treatment for the Prevention of Bare-Metal Stent Restenosis in Diabetic Patients

Abstract: Colchicine is associated with less neointimal hyperplasia and a decreased ISR rate when administered to diabetic patients after PCI with a BMS. This observation may prove useful in patients undergoing PCI in whom implantation of a drug-eluting stent is contraindicated or undesirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
138
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 23 publications
1
138
0
5
Order By: Relevance
“…Recently, a clinical trial supported this proposition, as colchicine was shown to be efficient to prevent restenosis after stent implantation [41] . The favorable effect of colchicine against restenosis could be explained by (1) its ability to disrupt the mitotic spindle by inhibiting the self-assembly of microtubules; (2) its potent antiinflammatory effect including the inhibition of neutrophils and macrophages; (3) the inhibition of the expression of cytokines (all of these aspects have been developed above); all of these processes have been largely involved in the pathophysiology of cellular hyperplasia and neointima formation leading to restenosis.…”
Section: Colchicine Promises For Cancer Therapy and Cardiovascular DImentioning
confidence: 98%
“…Recently, a clinical trial supported this proposition, as colchicine was shown to be efficient to prevent restenosis after stent implantation [41] . The favorable effect of colchicine against restenosis could be explained by (1) its ability to disrupt the mitotic spindle by inhibiting the self-assembly of microtubules; (2) its potent antiinflammatory effect including the inhibition of neutrophils and macrophages; (3) the inhibition of the expression of cytokines (all of these aspects have been developed above); all of these processes have been largely involved in the pathophysiology of cellular hyperplasia and neointima formation leading to restenosis.…”
Section: Colchicine Promises For Cancer Therapy and Cardiovascular DImentioning
confidence: 98%
“…Final pieces of evidence on colchicine use in secondary cardiovascular prevention became available more recently, with two large prospective studies pointing to the implications of 6-month colchicine therapy at a dose of 1 mg/daily for suppressing neointimal hyperplasia and reducing the incidence of coronary restenosis in patients with diabetes after baremetal stenting [102] and for decreasing inflammatory burden in patients with stable chronic heart failure [103]; and a much smaller, randomized, placebo-controlled trial of perioperative colchicine therapy (1 mg/day) starting 48 h before coronary artery bypass grafting and continuing 8 days thereafter (n = 59) revealed that the myocardial damage within 48 h post-operation was significantly less pronounced in the colchicine group than in the placebo group (based on levels of maximal hs-troponin T) [104].…”
Section: The Use Of Colchicine In Nonrheumatic Cardiovascular Disordersmentioning
confidence: 99%
“…The LoDoCo trial revealed that addition of low-dose colchicine of 500mcg daily to standard medical therapy significantly reduced the cardiovascular outcomes in patients with stable coronary artery disease (141). In another study, colchicine was found to be associated with less neointimal hyperplasia and in-stent restenosis in diabetic patients who had bare metal stents (142). A recent pilot study also suggested a potential benefit of colchicine in reducing infarct size when administered early to STEMI patients undergoing primary PCI (143).…”
Section: Anti-inflammatory Therapiesmentioning
confidence: 99%